Impact of Operating Cash Flow and ROA on Stock Returns in LQ 45 Companies in Period 2018-2023 - Margie, Lyandra Aisyah; Habibah, H. (Golden Ratio of Finance Management, 2025)
This study discusses the impact of operating cash flow and return on assets on stock returns in companies listed in the LQ 45 index on the Indonesia Stock Exchange (IDX) for 2018-2023. The purpose of this study is to assist investors in making better investment decisions by analyzing financial factors such as operating cash flow and return on assets that can affect stock returns. This study uses secondary data from the annual reports of 22 companies listed in the LQ 45, which are analyzed using panel data regression with the help of Eviews software. The study's results indicate that simultaneously and partially, operating cash flow and return on assets have a positive effect on stock returns. The higher the operating cash flow and return on a company's assets, the higher the stock returns investors receive. This finding supports the signal theory, which states that information companies provide through financial statements can be a positive signal to investors regarding the company's prospects. However, there are limitations in this study, such as the relatively short research period and limited sample size.